2011
DOI: 10.1007/s00210-011-0605-2
|View full text |Cite
|
Sign up to set email alerts
|

Different inhibitory effects of kynurenic acid and a novel kynurenic acid analogue on tumour necrosis factor-α (TNF-α) production by mononuclear cells, HMGB1 production by monocytes and HNP1-3 secretion by neutrophils

Abstract: Kynurenic acid (KynA), a broad spectrum antagonist of excitatory amino acid receptors, may serve as a protective agent in neurological disorders. The potential anti-inflammatory effect of KynA in human leukocytes has not been characterized. The aim of this study was to compare the effects of KynA with those of a new analogue, 2-(2-N,N-dimethylaminoethylamine-1-carbonyl)-1H-quinolin-4-one hydrochloride on tumour necrosis factor-α (TNF-α) production and high mobility group box protein 1 (HMGB1) secretion. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 43 publications
0
64
0
Order By: Relevance
“…The reference value of the KYNA concentration in a healthy man's plasma is measured in nanomoles, but rises to micromoles during inflammation. And it is this higher than the physiological level of KYNA that activates GPR35 receptors on cells of the immune system, producing an anti-inflammatory effect, mainly through the inhibition of secretion of pro-inflammatory cytokines (IL-1α, IFN-γ, TNF-α, HMGB1) by negative feedback [2,5,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference value of the KYNA concentration in a healthy man's plasma is measured in nanomoles, but rises to micromoles during inflammation. And it is this higher than the physiological level of KYNA that activates GPR35 receptors on cells of the immune system, producing an anti-inflammatory effect, mainly through the inhibition of secretion of pro-inflammatory cytokines (IL-1α, IFN-γ, TNF-α, HMGB1) by negative feedback [2,5,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…This development is rather scantily described in the literature and results of different studies are unequivocal. It is known that KYNA inhibits secretion of typical pro-inflammatory cytokines of macrophages (TNF-α), and it also depresses the release of HNP1-3α-defensin, which is recognized as an important marker of the activation of granulocytes, associated with an efficient destruction of microorganisms by these cells [5,17]. On the other hand, Barth et al [18] demonstrated an unquestionably stimulating effect of kynurenic acid on adhesion of monocytes and human neutrophils to the vascular endothelium, which -as the cited authors claim -suggests that KYNA can act as a chemokine and represents an important agent in the early stage of activation of phagocytic cells.…”
Section: Effect Of Dietary Administration Of Kynurenic Acid On the Acmentioning
confidence: 99%
“…In response to exogenous microbial products (such as endotoxin (Wang et al, 1999), CpG-DNA (Ivanov et al, 2007) (Jiang et al, 2005) lysophosphatidylcholine (LPC) (Gardella et al, 2002), or mycobacterial infection (Grover et al, 2008)) or endogenous host stimuli (e.g., TNF-α (Wang et al, 1999), IFN-α (Jiang and Pisetsky, 2006), IFN-β (Lu et al, 2014), IFN-γ (Rendon-Mitchell et al, 2003), hydrogen peroxide (Tang et al, 2007e), nitric oxide (Tamura et al, 2011), peroxynitrite (Loukili et al, 2011), hyperlipidemia (Haraba et al, 2011a), hyperglycemia (Kim et al, 2011a), kynurenic acid (Tiszlavicz et al, 2011), neuropeptide Y (Zhou et al, 2013a), ATP (Eun et al, 2014)) or other stimuli (ethanol (Whitman et al, 2013), photodynamic therapy (Korbelik et al, 2011), natural DNA or synthetic oligonucleotides (Jiang and Pisetsky, 2008b), and ultraviolet B (Chakraborty et al, 2013)), immune cells (e.g., macrophages, monocytes, neutrophils, DCs, NKs), fibroblasts, or epithelial cells actively release HMGB1 into the extracellular space. HMGB1 cannot be actively secreted via the classical endoplasmic reticulum-Golgi secretory pathway due to lack of a leader signal sequence.…”
Section: Hmgb1 Releasementioning
confidence: 99%
“…All available papers on the effect of KYNA on immunocompetent cells examined in vitro deal with the human peripheral blood leukocytes and focus on the influence of KYNA on the synthesis of pro-inflammatory cytokines following mitogenic stimulation of cells (Maes et al 2007, Fallarini et al 2010, Tiszlavicz et al 2011. To the authors' best knowledge, this is the first report describing the influence of kynurenic acid on the activity of fish immune cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Its anti-inflammatory effect stems from the effect on the GPR35 receptor. It is known that this receptor is not activated until KYNA reaches higher than physiological, micromole concentrations (Fallarini et al 2010, Mándi andVécsei 2012), and the major effect of its activation is the depressed synthesis of pro-inflammatory cytokines, nitrogen oxide and reactive oxygen species in immune cells (Maes et al 2007, Moroni et al 2007, Kaszaki et al 2008, Lugo-Huitron et al 2011, Tiszlavicz et al 2011, Małaczewska et al 2014. The above findings stimulate an interest in kynurenic acid as a potential immunomodulator, which could find applications in correcting the immune response of an organism, especially in the course of systemic disorders.…”
mentioning
confidence: 99%